Russia on the Danube - Taki, Viktor. (Budapest ; Vienna ; New York)
ix, 376 sayfa
Keywords: “One of the goals of Russia's Eastern policy was to turn Moldavia and Wallachia, the two Romanian principalities north of the Danube, from Ottoman vassals into a controllable buffer zone and a springboard for future military operations against Constantinople. Russia on the Danube describes the divergent interests and uneasy cooperation between the Russian officials and the Moldavian and Wallachian nobility in a key period between 1812 and 1834. The main conclusion of the book is that although Russian policy was driven by self-interest, and despite the Russophobia among a great part of the Romanian intellectuals, this turbulent period significantly contributed to the emergence, several decades later, of modern Romania.“ --